Obstacles affecting the use of scientific methods in time management of human resources at the Directorate of sports activity - Sabet, Siham H.; Tayeb, Nihad I. (Humanities Journal of University of Zakho, 2018)
The importance of research lies in knowing an identifying scientific methods of time management witch with enhance the chances of success and the development of human resources of the directorate of sports activity in the province of Basra . the problem of the study lies in the review of the obstacles that limit or preclude the investment of time management of human resources at the directorate of sport activity in a good way . the aim of the research is to identify the research aims to increase attention of how to invest the time by the human resources of directorate of sport activity in the province of Basra as an essential resource for the implementation of plans , policies and strategies . the researchers used the descriptive approach (including survey manner ). the study sample is the same study of population where the researcher distributed the research tool to all staff in the directorate of sports activity in Basra, whose numbers in the application of the study (22) employee. the researchers also refer in this section to the tools and means to collect information used in the research, with an explanation of tests used where the result were processed statistically by the statistical system (SPSS) used in the research . the most important conclusions and recommendations were that personal obstacles do not pose any negative hindrance affects the scientific method to manage time though remaining some obstacles that cannot be overcome, or neglected, poor efficiency is the most important organization . in any case these constraints did not exceed the average significantly reaching the top rated instrument, the technical and technological constrains of time management to a level that adversely affect or limit the scientific application of the method of time management and procrastination: not an obstacle is desirable to apply scientific methods to time management pursued by the sport activity directorate . concerning the recommendations, the researchers ask for the attention that should be paid to the organizational aspects in terms of time management and following scientific method and the promotion of artistic and technical aspects of time management and following the strategy and its components, processes, requirements of the operation and how to plan scientifically so as to ensure and end successfully and identify the factors that ensure the success of this system to perform a strategic role .